A New Method of Brain Plastination - Monir Taghipour; Mohammad Hossein Asadi; Mohsen Setayesh mehr; Zahed Safikhani; Abbas Ali Rabiei (Negah Institute for Scientific Communication, 2016)
Introduction: Plastination is a unique technique for preservation of biological specimens used for teaching purposes. The protocol of flexible sheet plastination includes fixation, slicing, dehydration, force impregnation, casting, and curing (Hajian, Rabiei, Fatollahpour & Esfandiary, 2008). The procedure is done by using P87 flexible unsaturated polyester resin and provides heavy, gross, fragile, and bubbling plastinated sheets. In this study, synthetic resin (P89) in the plastination laboratory at Isfahan Medical School is utilized with a new method for plastination of 3-mm human's brain slices without casting stage. Also, common plastination method with the use of P87 flexible resin was used and the products were evaluated and compared in the laboratory with new method products. This method is also compared with specimens made by P35 resin sandwich method. Methods: This study was carried out on 3 human brains. Initially, according to the conventional methods, the brains were fixed in 10% formaldehyde, cut sagitally, coronally, and horizontally into 3-mm thickness slices by meat slicer, and then dehydrated in cold acetone (-25°C) and immersed in P89 unsaturated polyester resin at 25°C. Finally, the specimens were taken out from vacuum chamber and exposed to room temperature. When both surfaces of specimens became dry, they were taken to P89 polyester resin pail again. We repeated this stage 10 times. Results: P35 specimens had high tensile strength compared to P89 specimens. Also P89 specimens had high bending capability compared to P35 specimens made by sandwich method. Likewise, P89 specimens were lighter compared to P35 specimens. In the naked survey of specimens, P35 specimens with white spot in the tissue indicate discoloration for plastination of brain specimens without casting stage. Conclusion: Our study showed that P89 technique is a cheap, quick, and less expensive method for producing sheet plastinated specimens which are suitable in teaching neuroanatomy.